2020
DOI: 10.1186/s12877-020-01867-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospital readmission in older adults within 30 days of discharge – a comparative retrospective study

Abstract: Background The area of hospital readmission in older adults within 30 days of discharge is extensively researched but few studies look at the whole process. In this study we investigated risk factors related, not only to patient characteristics prior to and events during initial hospitalisation, but also to the processes of discharge, transition of care and follow-up. We aimed to identify patients at most risk of being readmitted as well as processes in greatest need of improvement, the goal be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 50 publications
4
74
0
3
Order By: Relevance
“…The data in this study were retrieved from a larger study. The method of data collection has been previously described in detail [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data in this study were retrieved from a larger study. The method of data collection has been previously described in detail [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Older adults often suffer from several comorbidities thus leading to the use of multiple medications, both known risk factors concerning hospital readmission within 30 days of discharge [ 8 , 9 ]. This increased risk may be due to polypharmacy increasing the risk of medication errors [ 10 ] and medication-related problems such as adverse drug reactions [ 11 ] or drug-drug interactions [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding related to polypharmacy supports the result of a previous study, in which polypharmacy (daily administration of ≥5 medications) did not significantly increase the risk of readmission of older adults in Sweden. The previous study found the significant increase in risk of readmission only in older adults with excessive polypharmacy, defined as taking ≥10 drugs on a daily basis (OR, 1.66; p = 0.007) [ 10 ]. Polypharmacy was more related to very early readmission (day 0–1 post-discharge) than risk factors for 30-day readmission [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study used a 6-item Geriatric Brief Assessment (GBA) to predict 1-year readmission with C score of 0.58–0.61 [ 8 ]. Frailty [ 9 ], excessive polypharmacy[ 10 ], and caregiver burden[ 11 ] were previously suggested to be risk factors for readmission among older adults. Despite the existing evidence, few studies have explored the role of CGA in a scoring system to predict 30-day unplanned readmission in the older adult population.…”
Section: Introductionmentioning
confidence: 99%